HUBUNGAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI TERHADAP KESELAMATAN KERJA Di RSUD. DR. TENGKU MANSYUR KOTA TANJUNG BALAI - DADY HIDAYAH (JURNAL ILMIAH KOHESI, 2019)
Compliance with the use of PPE by health workers at work greatly affects personal safety. Compliance shown by a positive attitude can be influenced by high or low knowledge of the importance of using PPE. This study aims to determine the relationship between the behavior of the use of personal protective equipment to work safety in RSUD. Dr. Tengku mansyur tanjung balai city in 2018. This type of research is quantitative descriptive. The population of this research is 213 people, where the sample size is 68 people with proportional sample selection where data is taken using a questionnaire. Then the data is presented using a frequency distribution table.The results of this 68 employee research are generally in the good knowledge category of 93.7%, have a sufficient category of knowledge of 4.8% and less by 1.5%. Besides that the good attitude category was 89%, the moderate category attitude was 11%. In the good action category at 97.6%, the medium action at 2.4%. And finally in the category of PPE usage rates are also good at 85.9%, medium usage rates at 12.6% and less 1.5%.From the results of the study it is suggested to employees of the operational section together improve and maintain the habit of using personal protective equipment before doing work. especially regarding personal protective equipment to improve the knowledge of employees of the operational section, both from the government, the private sector and from the company itself.